International marketing in times of sustainability and digitalization - Graf, Erika (De Gruyter, 2023)
Given today's challenges, companies are confronted with pressing questions: Are marketing and sustainability a contradiction? How can digitalization support marketers beyond digital advertising? These questions must be addressed in an international context since, for most companies, international business is more a reality than just a strategic option as it was just a few decades ago. This book provides insights into the fundamentals of international marketing with a focus on these topics because they are commonplace in today's international marketing. It presents theories and concepts of international marketing in a concise form along with many real-world examples. The book explores how digitalization makes potential connections and advances available to marketing and how marketing can contribute to shaping a more sustainable future. It is a must read for students interested in the topic and managers who are confronted with these challenges. Supplementary materials for the book are available!